(untitled) (Journal of Environmental Science and Natural Resources, 2017)
Harvesting is one of the major costs for rice production. Although the use of machine for harvesting rice in Bangladesh is increasing day by day and the machines are either combine harvester or reaper and thresher. Farmers of Bangladesh don’t have specific information to the choice of these machines. So to determine the cost of use of each machine, a study was conducted in Doyalsara, Bogra and Mymensingh region. Data were collected for rice in the Aman and Boro season of 2015 to determine the cost of harvesting by combine harvester and reaping and threshing by reaper and thresher. It was found for combine harvester operational cost and for carrying rice bag and straw to the plot side was Tk.10,447/ha. On the other hand, for reaper and thresher, the reaping, binding, carrying the rice to the plot side, threshing and cleaning required Tk.6,940/ha. The percentage of cost of combine harvester in relation to reaper and thresher for the same work is higher by 50.53%. In the socio-economic condition of Bangladeshi farmers, harvesting and threshing operations done by using self-propelled reaper and close drum thresher is cost effective and reasonable. J. Environ. Sci. & Natural Resources, 10(1): 133-136 2017